Unusual structural changes going from Li+ to Cs+ in [W(CN)6(bpy)]2− ion salts: the Na+ case. Issue 24 (30th May 2021) - Hodorowicz, Maciej; Jurowska, Anna; Szklarzewicz, Janusz
Abstract : Two sodium salts with the [W(CN)6 (bpy)] 2− ion were synthesized and compared to Li +, K +, Rb + and Cs + structures. The comparison of molecular packing, inter- and intra-molecular interactions and cation properties is discussed. Abstract : Two complexes of the formula Na2 [W(CN)6 (bpy)]·6H2 O (1 ) and Na2 [W(CN)6 (bpy)]·5H2 O·CH3 CN (2 ) were synthesized, structurally characterized, described and compared with their lithium, potassium, rubidium and cesium analogues. This finalizes the description of structures of [W(CN)6 (bpy)] 2− ion salts with all alkali metals. The salts crystalize in the triclinic P 1̄ space group. In all the salts, layered structures are observed with weak hydrophobic bpy–bpy zipper like interactions between layers. The unexpected changes in W–W distance, thickness of layers, density and other parameters going from Li + to Cs + are described and discussed.